Nano rare earth nickel coating brass material and preparation method thereof
By modifying nano cerium oxide, the problem of agglomeration of nano rare earths in the electroplating solution is solved, and the uniform dispersion of rare earth elements in the brass plating layer is achieved, the brass crystals are refined, and the welding performance and mechanical strength are improved.
Patent Information
- Application Number
- CN202411648532.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-19
AI Technical Summary
In the prior art, nano rare earths are prone to agglomeration in the electroplating solution, resulting in uneven dispersion of rare earth elements in the brass plating layer and affecting welding performance.
By modifying the nano ceria, grafting the epoxy silane coupling agent and sodium alginate, the surface of the nano ceria is negatively charged, avoiding agglomeration, and dispersing evenly in the plating solution.
The inhibitory effect of rare earth elements on brass grain volume is improved, the brass crystal is refined, the welding performance and mechanical strength are improved, and the nickel-copper-zinc rare earth diffusion alloy layer is formed to enhance the bonding strength between the nickel-rare earth plating and brass.
Smart Images

Figure BDA0005140287560000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alloy materials, and in particular to a nano rare earth nickel plated brass material and a preparation method thereof. Background Art
[0002] Brass has a long history of use. As early as the ancient civilization period, people began to use brass to make decorations and practical tools. Ancient Rome and ancient China were pioneers in the use of brass. They used brass to make various exquisite crafts and tools. With the advent of the Industrial Revolution, the manufacturing and application technology of brass has developed rapidly. As an alloy material with a long history and wide application, brass plays an important role in many fields with its unique physical and chemical properties, such as construction, machinery manufacturing, electronics, automobiles and other fields. Brass is an alloy material based on copper and zinc. Its composition ratio and other added elements determine the specific properties and application fields of brass. The main components of brass are copper and zinc, of which the copper content is usually above 67% and the zinc content is above 32%. According to different application requirements, elements such as lead, tin, and nickel may also be added to brass to improve its performance. Due to the high temperature during the welding process of brass, a large amount of zinc in the brass will evaporate, resulting in a decrease in the corrosion resistance and mechanical properties of the brass material. In the prior art, a nickel layer is plated on the outer surface of the brass to prevent the loss of zinc in the brass material.
[0003] For example, Chinese patent publication number CN112323107 discloses a brass material with a nano rare earth nickel coating and a preparation method thereof, the method comprising mixing and dissolving NiSO4, NiCl2, H3BO3 and nano rare earth salt particles in water and using ultrasonic vibration to obtain a rare earth nickel electroplating solution; placing a brass substrate in the rare earth nickel electroplating solution for electroplating to obtain a brass covered with a nickel rare earth coating; and subjecting the brass covered with a nickel rare earth coating to vacuum heat treatment. This technical solution suppresses the enlargement of brass grains during welding by doping nano rare earths into the coating, thereby refining the brass grains and improving welding performance. However, nano rare earths are prone to agglomeration in the electroplating solution, resulting in uneven dispersion of rare earth elements in the brass coating, which in turn affects the inhibitory effect of rare earth elements on the volume of brass grains during welding, so that the brass grains need to be further refined to improve the welding performance of brass. Summary of the invention
[0004] In order to overcome the above problems of the prior art, the present invention provides a nano rare earth nickel plated brass material and a preparation method thereof. The nano rare earth nickel plated brass material prepared by the present invention has a smaller volume of brass grains formed during welding than the prior art and has good welding performance.
[0005] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:
[0006] A method for preparing a nano rare earth nickel plated brass material comprises the following steps:
[0007] 1) grinding the surface of the brass substrate with silicon dioxide sandpaper, then immersing it in deionized water for ultrasonic cleaning, and drying it in an oven to obtain a brass substrate without an oxide layer;
[0008] 2) immersing the deoxidized brass substrate in a degreasing liquid, continuing ultrasonic oscillation cleaning, and placing it in an oven for drying to obtain a degreased brass substrate;
[0009] 3) soaking the degreased brass substrate in a nitric acid solution, taking it out and placing it in deionized water for ultrasonic cleaning, soaking the cleaned brass substrate in a hydrofluoric acid solution, taking it out and placing it in deionized water for ultrasonic cleaning to obtain an activated brass substrate;
[0010] 4) adding nickel chloride, nickel sulfate, boric acid, modified nano cerium oxide and sodium dodecyl sulfate into deionized water, dispersing by ultrasonic oscillation to obtain an electroplating solution, placing an activated brass substrate in the electroplating solution as a cathode, and using a pure nickel plate as an anode to perform electroplating to obtain a nano rare earth nickel plated brass intermediate;
[0011] 5) drying the nano rare earth nickel-plated brass intermediate in an oven, and then placing it in a muffle furnace for vacuum heating and baking treatment to obtain a nano rare earth nickel-plated brass material.
[0012] The invention adds rare earth nano cerium oxide to the electroplating solution, which can inhibit the brass grains from becoming larger during the welding process, refine the brass grains, and improve the welding performance and mechanical strength. At the same time, a nickel-copper-zinc rare earth diffusion alloy layer is formed between the surface of the brass substrate and the nickel rare earth coating. The nickel-copper-zinc rare earth diffusion alloy layer can improve the bonding strength between the nickel rare earth coating and the brass, and can also prevent the zinc element from diffusing into the nickel rare earth coating. Compared with the ordinary nickel coating, it has better zinc retention performance and further improves the corrosion resistance and mechanical strength of the material.
[0013] Preferably, in step 2), the degreasing liquid comprises sodium hydroxide, sodium carbonate and sodium silicate.
[0014] Preferably, in step 3), the volume concentration of the nitric acid solution is 3-5%.
[0015] Preferably, in step 3), the volume concentration of the hydrofluoric acid solution is 10-20%.
[0016] Preferably, in step 4), the mass volume concentration of the modified nano-cerium oxide is 1-8 g / L.
[0017] Preferably, in step 4), the electroplating temperature is 40-50°C and the current density is 4-5A / dm 2 , the pH of the plating solution is maintained at 4-5, and the plating time is 1.5-3h.
[0018] Preferably, in step 4), the method for preparing modified nano-cerium oxide comprises the following steps:
[0019] Adding an epoxy silane coupling agent into an ethanol aqueous solution, heating and stirring, to obtain an epoxy silane coupling agent solution;
[0020] Adding nano-cerium oxide to epoxy silane coupling agent solution, heating and stirring to react, centrifugation, washing and drying to obtain silane coupling agent grafted modified nano-cerium oxide;
[0021] Sodium alginate is added into deionized water and stirred to dissolve to obtain a sodium alginate solution, silane coupling agent grafted modified nano cerium oxide is added into the sodium alginate solution, SnCl4 and HCl are added, heated and stirred to react, filtered, separated, washed and dried to obtain modified nano cerium oxide.
[0022] In the prior art, nano rare earth is doped into the coating to inhibit the brass grain from becoming larger during the welding process, so that the brass grain is refined and the welding performance is improved. However, nano rare earth is easy to agglomerate in the electroplating solution, resulting in uneven dispersion of rare earth elements in the brass coating, thereby affecting the inhibitory effect of rare earth elements on the volume of brass grains during welding. The present invention is to solve the above technical problems. By modifying nano cerium oxide, an epoxy silane coupling agent is first grafted on the surface of nano cerium oxide to load epoxy functional groups on the surface of nano cerium oxide, and then the epoxy silane coupling agent reacts with sodium alginate to graft sodium alginate to the surface of nano cerium oxide. Sodium alginate is ionized and negatively charged in an aqueous solution, so that the surface of nano cerium oxide is negatively charged. Under the action of electrostatic repulsion, nano cerium oxide is prevented from agglomerating, thereby improving the dispersion performance of nano cerium oxide in an aqueous solution, improving the inhibitory effect of rare earth elements on the volume of brass grains, and further refining brass crystals, thereby improving the welding performance of brass materials.
[0023] Preferably, the mass ratio of the nano-cerium oxide to the epoxy silane coupling agent is 1:0.2-0.8.
[0024] Preferably, the mass ratio of the silane coupling agent grafted modified nano-cerium oxide to sodium alginate is 1:0.4-0.7.
[0025] In order to fully disperse the nano cerium oxide and avoid its agglomeration, the surface of the nano cerium oxide must be loaded with a sufficient amount of sodium alginate. The mass ratio of the nano cerium oxide grafted with a silane coupling agent to the sodium alginate should be less than 1:0.4. However, the present invention team unexpectedly found that when the mass ratio of the nano cerium oxide grafted with a silane coupling agent to the sodium alginate should be less than 1:0.7, the thickness of the nickel-copper-zinc rare earth diffusion alloy layer formed between the surface of the brass substrate and the nickel rare earth coating was greatly reduced, resulting in a decrease in the zinc retention performance of the brass material, which was unexpected by the present invention team. This may be because the amount of sodium alginate grafted on the nano cerium oxide is too large, and its surface has a strong negative charge. The repulsive force between them prevents it from diffusing into the nickel coating, and the rare earth elements in the nickel coating are reduced, resulting in a reduction in the rare earth elements in the nickel-copper-zinc rare earth diffusion alloy layer, and then causing the thickness of the nickel-copper-zinc rare earth diffusion alloy layer to decrease. Therefore, the present invention strictly controls the mass ratio of the nano cerium oxide grafted with a silane coupling agent to the sodium alginate to be greater than 1:0.7.
[0026] A nano rare earth nickel plated brass material is prepared by the above method.
[0027] The present invention has the following beneficial effects:
[0028] 1) By adding rare earth nano-cerium oxide to the electroplating solution, the brass grains can be inhibited from becoming larger during the welding process, so that the brass grains are refined, and the welding performance and mechanical strength are improved. At the same time, a nickel-copper-zinc rare earth diffusion alloy layer is formed between the surface of the brass substrate and the nickel rare earth coating. The nickel-copper-zinc rare earth diffusion alloy layer can improve the bonding strength between the nickel rare earth coating and the brass, and can also prevent the zinc element from diffusing into the nickel rare earth coating. Compared with ordinary nickel coatings, it has better zinc retention performance and further improves the corrosion resistance and mechanical strength of the material;
[0029] 2) By modifying the nano-cerium oxide, the surface of the nano-cerium oxide is made negatively charged, and the electrostatic repulsion force prevents the nano-cerium oxide from agglomerating, thereby improving the dispersion performance of the nano-cerium oxide in the aqueous solution, improving the inhibitory effect of the rare earth element on the volume of the brass grains, and further refining the brass crystals, thereby improving the welding performance and mechanical properties of the brass material. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0031] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.
[0032] The brass matrix used in the specific implementation of the present invention is a brass matrix having a chemical formula of Cu 57 Zn 41.2 Fe 0.3 Pb 0.5 , the impurity content is 1%.
[0033] Example 1
[0034] A method for preparing a nano rare earth nickel plated brass material comprises the following steps:
[0035] 1) polishing the surface of the brass substrate with silica sandpaper, then immersing it in deionized water for ultrasonic cleaning for 20 minutes, and drying it in an oven to obtain a brass substrate without an oxide layer;
[0036] 2) immersing the deoxidized brass substrate in a degreasing solution, continuing ultrasonic oscillation cleaning for 30 minutes, and drying in an oven to obtain a degreasing brass substrate, wherein the degreasing solution comprises sodium hydroxide, sodium carbonate and sodium silicate, wherein the mass concentration of sodium hydroxide is 15 g / L, the mass concentration of sodium carbonate is 20 g / L, and the mass concentration of sodium silicate is 25 g / L;
[0037] 3) soaking the degreased brass substrate in a 4% nitric acid solution for 10 minutes, taking it out and placing it in deionized water for ultrasonic cleaning for 5 minutes, soaking the cleaned brass substrate in a 15% hydrofluoric acid solution for 10 minutes, taking it out and placing it in deionized water for ultrasonic cleaning for 5 minutes to obtain an activated brass substrate;
[0038] 4) adding nickel chloride, nickel sulfate, boric acid, modified nano-cerium oxide and sodium dodecyl sulfate into deionized water, and dispersing them by ultrasonic oscillation for 20 minutes to obtain an electroplating solution;
[0039] The electroplating solution contains 25g / L nickel chloride, 250g / L nickel sulfate, 20g / L boric acid, 7g / L modified nano cerium oxide, and 0.03g / L sodium dodecyl sulfate;
[0040] The activated brass substrate was placed in the electroplating solution as the cathode and the pure nickel plate as the anode for electroplating. The electroplating temperature was 45°C and the current density was 4.5A / dm 2 , the pH of the electroplating solution is maintained at 4.5, and the electroplating time is 2.5 h, to obtain a nano rare earth nickel plated brass intermediate;
[0041] 5) The nano rare earth nickel plated brass intermediate is placed in an oven and dried at 60° C., and then placed in a muffle furnace and subjected to vacuum heating and baking treatment at 500° C. for 3 h to obtain a nano rare earth nickel plated brass material.
[0042] The preparation method of modified nano cerium oxide comprises the following steps:
[0043] Add 2 g of epoxy silane coupling agent KH-560 into 150 mL of 60% ethanol aqueous solution, heat to 50° C. and stir for 1 h to obtain an epoxy silane coupling agent solution;
[0044] Adding nano-cerium oxide to epoxy silane coupling agent solution, the mass ratio of nano-cerium oxide to epoxy silane coupling agent is 1:0.7, heating to 60° C. and stirring for reaction for 2 hours, and then centrifugally separating, washing and drying to obtain nano-cerium oxide grafted with silane coupling agent;
[0045] 1.5 g of sodium alginate was added into 200 mL of deionized water and stirred to dissolve to obtain a sodium alginate solution. Nano-cerium oxide grafted with a silane coupling agent was added into the sodium alginate solution, wherein the mass ratio of nano-cerium oxide grafted with a silane coupling agent to sodium alginate was 1:0.6. 0.01 g of SnCl4 and 0.1 g of a 15% HCl solution were added, and the mixture was heated to 80° C. and stirred to react for 3 h. After filtration, separation, washing and drying, modified nano-cerium oxide was obtained.
[0046] Example 2
[0047] A method for preparing a nano rare earth nickel plated brass material comprises the following steps:
[0048] 1) polishing the surface of the brass substrate with silica sandpaper, then immersing it in deionized water for ultrasonic cleaning for 20 minutes, and drying it in an oven to obtain a brass substrate without an oxide layer;
[0049] 2) immersing the deoxidized brass substrate in a degreasing solution, continuing ultrasonic oscillation cleaning for 30 minutes, and drying in an oven to obtain a degreasing brass substrate, wherein the degreasing solution comprises sodium hydroxide, sodium carbonate and sodium silicate, wherein the mass concentration of sodium hydroxide is 15 g / L, the mass concentration of sodium carbonate is 20 g / L, and the mass concentration of sodium silicate is 25 g / L;
[0050] 3) soaking the degreased brass substrate in a 4% nitric acid solution for 10 minutes, taking it out and placing it in deionized water for ultrasonic cleaning for 5 minutes, soaking the cleaned brass substrate in a 15% hydrofluoric acid solution for 10 minutes, taking it out and placing it in deionized water for ultrasonic cleaning for 5 minutes to obtain an activated brass substrate;
[0051] 4) adding nickel chloride, nickel sulfate, boric acid, modified nano-cerium oxide and sodium dodecyl sulfate into deionized water, and dispersing them by ultrasonic oscillation for 20 minutes to obtain an electroplating solution;
[0052] The electroplating solution contains 25g / L nickel chloride, 250g / L nickel sulfate, 20g / L boric acid, 2g / L modified nano cerium oxide, and 0.03g / L sodium dodecyl sulfate;
[0053] The activated brass substrate was placed in the electroplating solution as the cathode and the pure nickel plate as the anode for electroplating. The electroplating temperature was 45°C and the current density was 4.5A / dm 2 , the pH of the electroplating solution was maintained at 4.5, and the electroplating time was 1.8 h, to obtain a nano rare earth nickel-plated brass intermediate;
[0054] 5) The nano rare earth nickel plated brass intermediate is placed in an oven and dried at 60° C., and then placed in a muffle furnace and subjected to vacuum heating and baking treatment at 500° C. for 3 h to obtain a nano rare earth nickel plated brass material.
[0055] The preparation method of modified nano cerium oxide comprises the following steps:
[0056] Add 2 g of epoxy silane coupling agent KH-560 into 150 mL of 60% ethanol aqueous solution, heat to 50° C. and stir for 1 h to obtain an epoxy silane coupling agent solution;
[0057] Adding nano-cerium oxide to epoxy silane coupling agent solution, the mass ratio of nano-cerium oxide to epoxy silane coupling agent is 1:0.3, heating to 60° C. and stirring for reaction for 2 hours, and then centrifugally separating, washing and drying to obtain nano-cerium oxide grafted with silane coupling agent;
[0058] 1.5 g of sodium alginate was added into 200 mL of deionized water and stirred to dissolve to obtain a sodium alginate solution. Nano-cerium oxide grafted with a silane coupling agent was added into the sodium alginate solution, wherein the mass ratio of nano-cerium oxide grafted with a silane coupling agent to sodium alginate was 1:0.45. 0.01 g of SnCl4 and 0.1 g of a 15% HCl solution were added, and the mixture was heated to 80° C. and stirred to react for 3 h. The modified nano-cerium oxide was obtained after filtration, separation, washing and drying.
[0059] Example 3
[0060] A method for preparing a nano rare earth nickel plated brass material comprises the following steps:
[0061] 1) polishing the surface of the brass substrate with silica sandpaper, then immersing it in deionized water for ultrasonic cleaning for 20 minutes, and drying it in an oven to obtain a brass substrate without an oxide layer;
[0062] 2) immersing the deoxidized brass substrate in a degreasing solution, continuing ultrasonic oscillation cleaning for 30 minutes, and drying in an oven to obtain a degreasing brass substrate, wherein the degreasing solution comprises sodium hydroxide, sodium carbonate and sodium silicate, wherein the mass concentration of sodium hydroxide is 15 g / L, the mass concentration of sodium carbonate is 20 g / L, and the mass concentration of sodium silicate is 25 g / L;
[0063] 3) soaking the degreased brass substrate in a 4% nitric acid solution for 10 minutes, taking it out and placing it in deionized water for ultrasonic cleaning for 5 minutes, soaking the cleaned brass substrate in a 15% hydrofluoric acid solution for 10 minutes, taking it out and placing it in deionized water for ultrasonic cleaning for 5 minutes to obtain an activated brass substrate;
[0064] 4) adding nickel chloride, nickel sulfate, boric acid, modified nano-cerium oxide and sodium dodecyl sulfate into deionized water, and dispersing them by ultrasonic oscillation for 20 minutes to obtain an electroplating solution;
[0065] The electroplating solution contains 25g / L nickel chloride, 250g / L nickel sulfate, 20g / L boric acid, 4g / L modified nano cerium oxide, and 0.03g / L sodium dodecyl sulfate;
[0066] The activated brass substrate was placed in the electroplating solution as the cathode and the pure nickel plate as the anode for electroplating. The electroplating temperature was 45°C and the current density was 4.5A / dm 2 , the pH of the electroplating solution is maintained at 4.5, the electroplating time is 2 hours, and a nano rare earth nickel-plated brass intermediate is obtained;
[0067] 5) The nano rare earth nickel plated brass intermediate is placed in an oven and dried at 60° C., and then placed in a muffle furnace and subjected to vacuum heating and baking treatment at 500° C. for 3 h to obtain a nano rare earth nickel plated brass material.
[0068] The preparation method of modified nano cerium oxide comprises the following steps:
[0069] Add 2 g of epoxy silane coupling agent KH-560 into 150 mL of 60% ethanol aqueous solution, heat to 50° C. and stir for 1 h to obtain an epoxy silane coupling agent solution;
[0070] Adding nano-cerium oxide to epoxy silane coupling agent solution, the mass ratio of nano-cerium oxide to epoxy silane coupling agent is 1:0.5, heating to 60° C. and stirring for reaction for 2 hours, and then centrifugally separating, washing and drying to obtain nano-cerium oxide grafted with silane coupling agent;
[0071] 1.5 g of sodium alginate was added into 200 mL of deionized water and stirred to dissolve to obtain a sodium alginate solution. Nano-cerium oxide grafted with a silane coupling agent was added into the sodium alginate solution, wherein the mass ratio of nano-cerium oxide grafted with a silane coupling agent to sodium alginate was 1:0.5. 0.01 g of SnCl4 and 0.1 g of a 15% HCl solution were added, and the mixture was heated to 80° C. and stirred to react for 3 h. After filtration, separation, washing and drying, modified nano-cerium oxide was obtained.
[0072] Example 4
[0073] A method for preparing a nano rare earth nickel plated brass material comprises the following steps:
[0074] 1) polishing the surface of the brass substrate with silica sandpaper, then immersing it in deionized water for ultrasonic cleaning for 20 minutes, and drying it in an oven to obtain a brass substrate without an oxide layer;
[0075] 2) immersing the deoxidized brass substrate in a degreasing solution, continuing ultrasonic oscillation cleaning for 30 minutes, and drying in an oven to obtain a degreasing brass substrate, wherein the degreasing solution comprises sodium hydroxide, sodium carbonate and sodium silicate, wherein the mass concentration of sodium hydroxide is 15 g / L, the mass concentration of sodium carbonate is 20 g / L, and the mass concentration of sodium silicate is 25 g / L;
[0076] 3) soaking the degreased brass substrate in a 5% nitric acid solution for 10 minutes, taking it out and placing it in deionized water for ultrasonic cleaning for 5 minutes, soaking the cleaned brass substrate in a 20% hydrofluoric acid solution for 10 minutes, taking it out and placing it in deionized water for ultrasonic cleaning for 5 minutes to obtain an activated brass substrate;
[0077] 4) adding nickel chloride, nickel sulfate, boric acid, modified nano-cerium oxide and sodium dodecyl sulfate into deionized water, and dispersing them by ultrasonic oscillation for 20 minutes to obtain an electroplating solution;
[0078] The electroplating solution contains 25g / L nickel chloride, 250g / L nickel sulfate, 20g / L boric acid, 8g / L modified nano cerium oxide, and 0.03g / L sodium dodecyl sulfate;
[0079] The activated brass substrate was placed in the electroplating solution as the cathode and the pure nickel plate as the anode for electroplating. The electroplating temperature was 50°C and the current density was 5A / dm 2 , the pH of the electroplating solution is maintained at 5, the electroplating time is 3 hours, and a nano rare earth nickel-plated brass intermediate is obtained;
[0080] 5) The nano rare earth nickel plated brass intermediate is placed in an oven and dried at 60° C., and then placed in a muffle furnace and subjected to vacuum heating and baking treatment at 500° C. for 3 h to obtain a nano rare earth nickel plated brass material.
[0081] The preparation method of modified nano cerium oxide comprises the following steps:
[0082] Add 2 g of epoxy silane coupling agent KH-560 into 150 mL of 60% ethanol aqueous solution, heat to 50° C. and stir for 1 h to obtain an epoxy silane coupling agent solution;
[0083] Adding nano-cerium oxide to epoxy silane coupling agent solution, the mass ratio of nano-cerium oxide to epoxy silane coupling agent is 1:0.8, heating to 60° C. and stirring for reaction for 2 hours, and then centrifugally separating, washing and drying to obtain nano-cerium oxide grafted with silane coupling agent;
[0084] 1.5 g of sodium alginate was added into 200 mL of deionized water and stirred to dissolve to obtain a sodium alginate solution. Nano-cerium oxide grafted with a silane coupling agent was added into the sodium alginate solution, wherein the mass ratio of nano-cerium oxide grafted with a silane coupling agent to sodium alginate was 1:0.7. 0.01 g of SnCl4 and 0.1 g of a 15% HCl solution were added, and the mixture was heated to 80° C. and stirred to react for 3 h. The modified nano-cerium oxide was obtained after filtration, separation, washing and drying.
[0085] Example 5
[0086] A method for preparing a nano rare earth nickel plated brass material comprises the following steps:
[0087] 1) polishing the surface of the brass substrate with silica sandpaper, then immersing it in deionized water for ultrasonic cleaning for 20 minutes, and drying it in an oven to obtain a brass substrate without an oxide layer;
[0088] 2) immersing the deoxidized brass substrate in a degreasing solution, continuing ultrasonic oscillation cleaning for 30 minutes, and drying in an oven to obtain a degreasing brass substrate, wherein the degreasing solution comprises sodium hydroxide, sodium carbonate and sodium silicate, wherein the mass concentration of sodium hydroxide is 15 g / L, the mass concentration of sodium carbonate is 20 g / L, and the mass concentration of sodium silicate is 25 g / L;
[0089] 3) soaking the degreased brass substrate in a 3% nitric acid solution for 10 minutes, taking it out and placing it in deionized water for ultrasonic cleaning for 5 minutes, soaking the cleaned brass substrate in a 10% hydrofluoric acid solution for 10 minutes, taking it out and placing it in deionized water for ultrasonic cleaning for 5 minutes to obtain an activated brass substrate;
[0090] 4) adding nickel chloride, nickel sulfate, boric acid, modified nano-cerium oxide and sodium dodecyl sulfate into deionized water, and dispersing them by ultrasonic oscillation for 20 minutes to obtain an electroplating solution;
[0091] The electroplating solution contains 25g / L nickel chloride, 250g / L nickel sulfate, 20g / L boric acid, 1g / L modified nano cerium oxide, and 0.03g / L sodium dodecyl sulfate;
[0092] The activated brass substrate was placed in the electroplating solution as the cathode and the pure nickel plate as the anode for electroplating. The electroplating temperature was 40°C and the current density was 4A / dm 2 , the pH of the electroplating solution is maintained at 4, the electroplating time is 1.5h, and a nano rare earth nickel plated brass intermediate is obtained;
[0093] 5) The nano rare earth nickel plated brass intermediate is placed in an oven and dried at 60° C., and then placed in a muffle furnace and subjected to vacuum heating and baking treatment at 500° C. for 3 h to obtain a nano rare earth nickel plated brass material.
[0094] The preparation method of modified nano cerium oxide comprises the following steps:
[0095] Add 2 g of epoxy silane coupling agent KH-560 into 150 mL of 60% ethanol aqueous solution, heat to 50° C. and stir for 1 h to obtain an epoxy silane coupling agent solution;
[0096] Adding nano-cerium oxide to epoxy silane coupling agent solution, the mass ratio of nano-cerium oxide to epoxy silane coupling agent is 1:0.2, heating to 60° C. and stirring for reaction for 2 hours, and then centrifugally separating, washing and drying to obtain nano-cerium oxide grafted with silane coupling agent;
[0097] 1.5 g of sodium alginate was added into 200 mL of deionized water and stirred to dissolve to obtain a sodium alginate solution. Nano-cerium oxide grafted with a silane coupling agent was added into the sodium alginate solution, wherein the mass ratio of nano-cerium oxide grafted with a silane coupling agent to sodium alginate was 1:0.4. 0.01 g of SnCl4 and 0.1 g of a 15% HCl solution were added, and the mixture was heated to 80° C. and stirred to react for 3 h. The modified nano-cerium oxide was obtained after filtration, separation, washing and drying.
[0098] Comparative Example 1
[0099] The difference between Comparative Example 1 and Example 1 is that:
[0100] Nano cerium oxide is not modified.
[0101] The remaining steps are the same as those in Example 1.
[0102] Comparative Example 2
[0103] The difference between Comparative Example 2 and Example 5 is:
[0104] During the preparation of modified nano-cerium oxide,
[0105] The mass ratio of silane coupling agent grafted modified nano-cerium oxide to sodium alginate is 1:0.3.
[0106] The remaining steps are the same as those in Example 5.
[0107] Comparative Example 3
[0108] The difference between Comparative Example 3 and Example 4 is that:
[0109] The mass ratio of silane coupling agent grafted modified nano-cerium oxide to sodium alginate is 1:0.8.
[0110] The remaining steps are the same as those in Example 4.
[0111] Comparative Example 4
[0112] The difference between Comparative Example 4 and Example 4 is that:
[0113] The mass ratio of silane coupling agent grafted modified nano-cerium oxide to sodium alginate is 1:0.9.
[0114] The remaining steps are the same as those in Example 4.
[0115] Comparative Example 5
[0116] The difference between Comparative Example 5 and Example 4 is that:
[0117] The mass ratio of silane coupling agent grafted modified nano-cerium oxide to sodium alginate is 1:1.
[0118] The remaining steps are the same as those in Example 4.
[0119] Comparative Example 6
[0120] The difference between Comparative Example 5 and Example 4 is that:
[0121] The mass ratio of silane coupling agent grafted modified nano-cerium oxide to sodium alginate is 1:1.5.
[0122] The remaining steps are the same as those in Example 4.
[0123] Performance Testing
[0124] The nano rare earth nickel plated brass material obtained in the embodiment and the comparative example was reflowed at 200° C. for 15 seconds and then welded to a PCB board to obtain a welded part. The thickness of the coating and the diffusion layer were tested using the "GB / T6462-2005 Metal and Oxide Covering Thickness Measurement Microscope Method", and the grain size of the brass matrix after welding was measured according to the "ASTME112-2013 Standard Test Method for Determination of Average Grain Size", and the zinc content in the brass matrix was tested and confirmed using the "GB-T15074-2008 General Rules for Electron Probe Quantitative Analysis Methods".
[0125]
[0126] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a nano rare earth nickel plated brass material, characterized in that: The following steps are involved: 1) grinding the surface of the brass substrate with silicon dioxide sandpaper, then immersing it in deionized water for ultrasonic cleaning, and drying it in an oven to obtain a brass substrate without an oxide layer; 2) immersing the deoxidized brass substrate in a degreasing liquid, continuing ultrasonic oscillation cleaning, and placing it in an oven for drying to obtain a degreased brass substrate; 3) soaking the degreased brass substrate in a nitric acid solution, taking it out and placing it in deionized water for ultrasonic cleaning, soaking the cleaned brass substrate in a hydrofluoric acid solution, taking it out and placing it in deionized water for ultrasonic cleaning to obtain an activated brass substrate; 4) adding nickel chloride, nickel sulfate, boric acid, modified nano cerium oxide and sodium dodecyl sulfate into deionized water, dispersing by ultrasonic oscillation to obtain an electroplating solution, placing an activated brass substrate in the electroplating solution as a cathode, and using a pure nickel plate as an anode to perform electroplating to obtain a nano rare earth nickel plated brass intermediate; 5) drying the nano rare earth nickel-plated brass intermediate in an oven, and then placing it in a muffle furnace for vacuum heating and baking treatment to obtain a nano rare earth nickel-plated brass material.
2. The method for preparing a nano rare earth nickel-plated brass material according to claim 1, characterized in that: In the step 2), the degreasing liquid includes sodium hydroxide, sodium carbonate and sodium silicate.
3. The method for preparing a nano rare earth nickel plated brass material according to claim 1, characterized in that: In the step 3), the volume concentration of the nitric acid solution is 3-5%.
4. The method for preparing a nano rare earth nickel-plated brass material according to claim 1, characterized in that: In the step 3), the volume concentration of the hydrofluoric acid solution is 10-20%.
5. The method for preparing a nano rare earth nickel plated brass material according to claim 1, characterized in that: In the step 4), the mass volume concentration of the modified nano-cerium oxide is 1-8 g / L.
6. The method for preparing a nano rare earth nickel plated brass material according to claim 1, characterized in that: In the step 4), the electroplating temperature is 40-50° C., the current density is 4-5 A / dm 2 , the pH of the electroplating solution is maintained at 4-5, and the electroplating time is 1.5-3 h.
7. The method for preparing a nano rare earth nickel plated brass material according to claim 1, characterized in that: In the step 4), the preparation method of modified nano cerium oxide comprises the following steps: Adding an epoxy silane coupling agent into an ethanol aqueous solution, heating and stirring, to obtain an epoxy silane coupling agent solution; Adding nano-cerium oxide to epoxy silane coupling agent solution, heating and stirring to react, centrifugation, washing and drying to obtain silane coupling agent grafted modified nano-cerium oxide; Sodium alginate is added into deionized water and stirred to dissolve to obtain a sodium alginate solution, silane coupling agent grafted modified nano cerium oxide is added into the sodium alginate solution, SnCl4 and HCl are added, heated and stirred to react, filtered, separated, washed and dried to obtain modified nano cerium oxide.
8. The method for preparing a nano rare earth nickel plated brass material according to claim 7, characterized in that: The mass ratio of the nano cerium oxide to the epoxy silane coupling agent is 1:0.2-0.
8.
9. The method for preparing a nano rare earth nickel plated brass material according to claim 7, characterized in that: The mass ratio of the silane coupling agent grafted modified nano cerium oxide to sodium alginate is 1:0.4-0.
7.
10. A nano rare earth nickel plated brass material, characterized in that: The method is prepared by any one of claims 1 to 9.
Citation Information
Patent Citations
Nano-particle composite electroplating solution for scaffolds
CN106119908A
Brass material with nano rare earth nickel coating and preparation method for brass material
CN112323107A